Desenvolvimento sustentável e tributação: o papel do tributo ambiental no Brasil - Fernandes, André Luiz Fonseca (2007)
The main purpose of this masters thesis is to investigate the role of the sustainable development principle in Brazilian Environmental Tax Law. Sustainable development is not merely a slogan, as many people think. In fact, its main outlines are contained both in International Law (Declaration of the United Nations Conference on Environment and Development ECO-92) and Brazilian Federal Constitution. These outlines reveal dimensions of an economic, social, political and environmental nature. All of these dimensions connect sustainable development with Environmental Law, particularly with the polluter pays principle. The polluter pays principle is fundamentally concerned with the issue of cost allocation: the polluter should be the entity to pay for the pollution. This principle can be implemented through direct regulation (command-and-control regulation) or market-based instruments, such as tradable emission rights or taxation. Environmental taxes are properly levied only if in compliance with sustainable development principle.